Biogenic Amines in Portuguese Traditional Foods and Wines: a review - Ferreira, Isabel (2006)
The presence of biogenic amines in foodstuffs is an important food safety problem because of the implication of these compounds in food intolerance and intoxication. The separation and quantification of biogenic amines in foods is normally performed by chromatographic techniques. This review contains descriptions of the quantification of biogenic amines in Portuguese traditional fermented and/or ripened foods and wines, including Protected Denomination of Origin cheeses, drycured sausages, and Portuguese wines (including Port wines), using different analytical methods based on high-pressure liquid chromatography (UV or diode array and/or fluorometric detectors) and gas chromatography (with a mass spectrometry detector). The evolution of biogenic amines during fermentation, ripening, aging, or storage of those products was also evaluated. Biogenic amine concentrations ranged widely within individual food items, and storage, transport, and handling conditions can influence to some extent the biogenic amines present and their concentrations. Traditional foods are an important part of the Portuguese diet, and a high intake of harmful amounts of biogenic amines from traditional Portuguese fermented foods is possible. However, extensive research is needed to extend the current limited database.